2007
DOI: 10.1158/1541-7786.mcr-06-0358
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Methylation Events during Colorectal Tumor Progression by Absolute Quantitative Analysis of Methylated Alleles

Abstract: To date, the epigenetic events involved in the progression of colorectal cancer are not well described. To study, in detail, methylation during colorectal cancer development in high-risk adenomas, we developed an assay combining in situ (on-slide) sodium bisulfite modification (SBM) of paraffin-embedded archival tissue sections with absolute quantitative assessment of methylated alleles (AQAMA). We tested the performance of the assay to detect methylation level differences between paired pre-malignant and mali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 35 publications
3
44
0
Order By: Relevance
“…Before and after sodium bisulfite modification, double-stranded and single-stranded DNA were quantified using PicoGreen and OliGreen assays (Molecular Probes; Invitrogen), respectively. Sufficient input DNA for AQAMA was determined as described (17). To assess background signal, a salmon sperm DNA sample without tumor DNA was included in all assays in triplicate.…”
Section: Translational Relevancementioning
confidence: 99%
See 3 more Smart Citations
“…Before and after sodium bisulfite modification, double-stranded and single-stranded DNA were quantified using PicoGreen and OliGreen assays (Molecular Probes; Invitrogen), respectively. Sufficient input DNA for AQAMA was determined as described (17). To assess background signal, a salmon sperm DNA sample without tumor DNA was included in all assays in triplicate.…”
Section: Translational Relevancementioning
confidence: 99%
“…Primary tumor methylation levels of MINT loci 1, 2, 3, 12, 17, 25, and 31 were assessed by AQAMA in triplicate (17). Controls for specificity of AQAMA for both methylated and unmethylated sequences, as well as controls for nonspecific amplification, were included (17,27).…”
Section: Translational Relevancementioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, there is increasing evidence that age affects normal colonic mucosa and tumors. For instance, DNA methylation has been shown to increase with age in normal colonic mucosa [30,35] and different protein expression patterns have been found in the colonic mucosa of the elderly compared to that of younger people [26]. Moreover, Morris et al have also shown that the molecular aberrations in tumors differ according to age [34].…”
Section: Discussionmentioning
confidence: 99%